Beam dynamics design of a thermionic gun-based LINAC injector for a THz-FEL oscillator - Amin Ali Sadraei Javaheri; Fazel Jahangiri; Shahin Sanaye Hajari; Ali Reza Niknam (Results in Physics)
The broad and diverse applications of intense terahertz radiation have motivated many laboratories around the world in order to develop facilities based on the rapidly developing technology of terahertz free electron laser (THz-FEL). A key component of such a system is its linear accelerator (linac) that provides the required intense and high-quality electron beam. As a part of Nuclear Science and Technology Research Institute High Power Linac (NSTRI-HPL) project, the development of a THz-FEL is underway. This paper presents the beam dynamics design of its electron injector. Based on domestic capabilities, this system consists of a thermionic electron gun followed by a pre-buncher, a long Travelling Wave (TW) buncher and accelerating structures that provides a beam of 8 MeV energy with a pulse current up to 1 A. Cares has been taken in order to end up with a beam of lower emittance, bunch length and energy spread. This is mainly the responsibility of the bunching system. Here a special design of a travelling wave buncher has been presented based on the new concept of the low gradient bunching. The resulting normalized beam emittance, rms bunch length and the relative energy spread are 17.5 mm-mrad, 8 ps and 1.4 % respectively. At the end, the injector performance has been compared with some existing THz-FEL facilities worldwide.